2015
DOI: 10.1039/c5lc00226e
|View full text |Cite
|
Sign up to set email alerts
|

Size and deformability based separation of circulating tumor cells from castrate resistant prostate cancer patients using resettable cell traps

Abstract: The enumeration and capture of circulating tumor cells (CTCs) are potentially of great clinical value as they offer a non-invasive means to access tumor materials to diagnose disease and monitor treatment efficacy. Conventional immunoenrichment of CTCs may fail to capture cells with low surface antigen expression. Micropore filtration presents a compelling label-free alternative that enriches CTCs using their biophysical rather than biochemical characteristics. However, this strategy is prone to clogging of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 49 publications
0
60
0
Order By: Relevance
“…Recently, Qin et al (43) used the resettable cell trap mechanism to separate cells based on their size and deformability using an adjustable aperture that can be periodically cleared to prevent clogging. This system was able to capture ≥5 CTCs in 18/22 (82%) patients with a mean count of 257 in 7.5 ml of whole blood, while the CellSearch system found ≥5 CTCs in 9/22 (41%) metastatic castration-resistant PCa (mCRPC) with a mean count of 25 in the 7.5 ml whole blood samples.…”
Section: Enrichment and Detection Strategies For Ctcmentioning
confidence: 99%
“…Recently, Qin et al (43) used the resettable cell trap mechanism to separate cells based on their size and deformability using an adjustable aperture that can be periodically cleared to prevent clogging. This system was able to capture ≥5 CTCs in 18/22 (82%) patients with a mean count of 257 in 7.5 ml of whole blood, while the CellSearch system found ≥5 CTCs in 9/22 (41%) metastatic castration-resistant PCa (mCRPC) with a mean count of 25 in the 7.5 ml whole blood samples.…”
Section: Enrichment and Detection Strategies For Ctcmentioning
confidence: 99%
“…After CTC capture, flow in the opposite direction releases captured CTCs for harvesting and subsequent molecular characterization. The Resettable Cell Trap (RCT) uses a strategy similar to Parsortix, but, instead of decreasing the channel height, the microdevice uses pneumatically-controlled microvalves to alter the aperture of the flow channel and entrap CTCs in 'pockets' with a height greater than the main channel (Qin et al, 2015). Relaxation of the microvalve causes an increase in the aperture and subsequent release of captured CTCs.…”
Section: Three-dimensional Microfiltration Systemsmentioning
confidence: 99%
“…Constructed from parylene-C, can process WB, captures viable cells, clusters observed Kaifi et al, 2015) 3D FaCTChecker Constructed from parylene-C, captures viable cells between membrane layers Parsortix Viable cells released by reversing flow Resettable Cell Trap Pneumatically-controlled microvalves (Qin et al, 2015) Cluster Chip Triangular pillars designed for CTC clusters (Sarioglu et al, 2015) Biophysical e Inertial Focusing Cells are passively separated by size through the application of inertial forces in microfluidic devices that affect positioning within the flow channel.…”
Section: D Track-etched Isetmentioning
confidence: 99%
“…Whereas some have posited that CTCs have low deformability 13,37 and may need to maintain a more solid-like state, potentially to lodge in the microcirculation of particular peripheral sites, 28 many studies have suggested CTCs should be more deformable than normal cells, 18,3842 potentially as a requirement for intravasation or even for resisting immune responses from mediators such as cytotoxic T lymphocytes which employ synaptic forces to accelerate targeted cell death. 43 Our findings are similar with the latter and Chen et al 30 , who show that 4 primary prostate cancer CTCs displayed highly deformable phenotypes, characteristic of high metastatic potential.…”
Section: Resultsmentioning
confidence: 99%